Trigonal Cu2-II-Sn-VI4 (II = Ba, Sr and VI = S, Se) quaternary compounds for earth-abundant photovoltaics. Issue 6 (25th January 2016) - Hong, Feng; Lin, Wenjun; Meng, Weiwei; Yan, Yanfa
Abstract : We propose trigonal Cu2 -II-Sn-VI4 (II = Ba, Sr and VI = S, Se) quaternary compounds for earth-abundant solar cell applications. Abstract : We propose trigonal Cu2 -II-Sn-VI4 (II = Ba, Sr and VI = S, Se) quaternary compounds for earth-abundant solar cell applications. Through density functional theory calculations, we show that these compounds exhibit similar electronic and optical properties to kesterite Cu2 ZnSnS4 (CZTS): high optical absorption with band gaps suitable for efficient single-junction solar cell applications. However, the trigonal Cu2 -II-Sn-VI4 compounds exhibit defect properties more suitable for photovoltaic applications than those of CZTS. In CZTS, the dominant defects are the deep acceptors, Cu substitutions on Zn sites, which cause non-radiative recombination and limit the open-circuit voltages of CZTS solar cells. On the contrary, the dominant defects in trigonal Cu2 -II-Sn-VI4 are the shallow acceptors, Cu vacancies, similar to those in CuInSe2 . Our results suggest that the trigonal Cu2 -II-Sn-VI4 quaternary compounds could be promising candidates for efficient earth-abundant thin-film solar cell and photoeletrochemical water-splitting applications.